Characterisation of the Australian Nacophorini using adult morphology, and phylogeny of the Geometridae based on morphological characters - Young, Catherine J. (Zootaxa, 2008)
The Australian Nacophorini and related taxa are described using a matrix of 116 adult morphological characters. Adults of 72 species are illustrated using photographs and electron micrographs. Subsets of the characters are used to conduct a phylogenetic analysis based on cladistic principles. The adult morphological character set was augmented with 17 characters from eggs and 27 from larvae. The resulting phylogeny is poorly resolved but provides support for many of the relationships recovered by previous molecular analyses of the group, including basal derivations for characters of Larentiinae and Sterrhinae relative to those of the rest of Geometridae, and the monophyly of the Geometrinae + Oenochrominae s. str. Combining 28S D2 datawith morphological data produced a matrix of 60 taxa and 590 characters. The majority rule consensus tree produced by the combined morphological and 28S D2 data is almost identical to the majority rule consensus tree produced by the 28S D2 data alone, except that bootstrap support is lower for most nodes. Common clades obtained from the molecular and morphological trees are described in terms of morphological data. On this basis a concept of the Australian Nacophorini includes Lithinini and Australian Archiearinae. Two robust groups within the tribe also are delimited using characters from all data sources. Comparsions are made between the Nearctic and Neotropical Nacophorini on the basis of shared morphological characters. Australian Boarmiini are defined by synapomorphies.